ANALISIS TINGKAT KENYAMANAN TERMAL DI KOTA DUMAI MENGGUNAKAN TEMPERATURE HUMIDITY INDEX - Putri Santy Siregar (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
Dumai City as a port and industrial city, plays an important role in economic growth in Riau Province. This thing has led to rapid development in various sectors. The development results in reduced areas of vegetation cover and green open space (RTH) areas and affects the level of physiological comfort in an area. This study aims to find out how much the comfortable level of Dumai City as an industrial area using the Temperature Humidity Index (THI) method. The data used in this stydy are the daily average air temperature and relative humidity for the period 1991-2020 from the meteorological observation station at Pinang Kampai Dumai Airport. This study showed that the level of thermal comfortable using air temperature and relative humidity data by the THI index is generally only part of the urban population (0.4%) who feel comfortable, with the most comfortable category being 78.2% and the uncomfortable category being 21.4%.